On the kinetic decomposition voltage of ternary oxides. Issue 4 (8th January 2018) - Chun, Jakyu; Martin, Manfred; Yoo, Han-Ill
Abstract : The theoretical and experimental kinetic decomposition voltage in a ternary oxide under electric driving force. Abstract : In a previous article the authors reported the kinetic unmixing and decomposition of the ternary oxide NiTiO3 by an externally applied voltage. It was found [J. Chun, et al., J. Appl. Phys., 117, 2015, 124504] that while kinetic unmixing occurred for all magnitudes of the applied voltage, kinetic decomposition occurred only above a certain threshold voltage U kind. The experimentally determined value of U kind, however, did not coincide with the thermodynamic expectation according to the definition by Gibbs ( ). In this work the kinetic decomposition voltage U kind of a ternary oxide ABO ν is theoretically derived and compared with the experimental results. It turns out that U kind depends on the mobility ratio of the cations and agrees with observed results for the system of NiTiO3 within the error bounds.